Characterization of new allele influencing flowering time in bread wheat introgressed from Triticum militinae - Ivaničová, Zuzana; Jakobson, Irena; Reis, Diana; Šafář, Jan; Milec, Zbyněk; Abrouk, Michael; Doležel, Jaroslav; Järve, Kadri; Valárik, Miroslav (New biotechnology, 2016)
Flowering time variation was identified within a mapping population of doubled haploid lines developed from a cross between the introgressive line 8.1 and spring bread wheat cv. Tähti. The line 8.1 carried introgressions from tetraploid Triticum militinae in the cv. Tähti genetic background on chromosomes 1A, 2A, 4A, 5A, 7A, 1B and 5B. The most significant QTL for the flowering time variation was identified within the introgressed region on chromosome 5A and its largest effect was associated with the VRN-A1 locus, accounting for up to 70% of phenotypic variance. The allele of T. militinae origin was designated as VRN-A1f-like. The effect of the VRN-A1f-like allele was verified in two other mapping populations. QTL analysis identified that in cv. Tähti and cv. Mooni genetic background, VRN-A1f-like allele incurred a delay of 1.9-18.6 days in flowering time, depending on growing conditions. Sequence comparison of the VRN-A1f-like and VRN-A1a alleles from the parental lines of the mapping populations revealed major mutations in the promoter region as well as in the first intron, including insertion of a MITE element and a large deletion. The sequence variation allowed construction of specific diagnostic PCR markers for VRN-A1f-like allele determination. Identification and quantification of the effect of the VRN-A1f-like allele offers a useful tool for wheat breeding and for studying fine-scale regulation of flowering pathways in wheat.
Keywords: Triticum; Bread; lokus kvantitativního znaku; Genes, Plant; chléb; rostlinné geny; pšenice; Alleles; Breeding; květy; Flowers; alely; roční období; Seasons; Quantitative Trait Loci; Biotechnology; biotechnologie; chov